2016
DOI: 10.1016/j.celrep.2016.10.032
|View full text |Cite
|
Sign up to set email alerts
|

CD8 + T Lymphocyte Self-Renewal during Effector Cell Determination

Abstract: SUMMARY Selected CD8+ T cells must divide, produce differentiated effector cells, and self-renew, often repeatedly. We now show that silencing expression of the transcription factor TCF1 marks loss of self-renewal by determined effector cells, and that this requires cell division. In acute infections, the first three CD8+ T cell divisions produce daughter cells with unequal proliferative signaling but uniform maintenance of TCF1 expression. The more quiescent initial daughter cells resemble canonical central m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
122
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(164 citation statements)
references
References 34 publications
14
122
0
Order By: Relevance
“…While mice infused with untreated cells were mainly effectors with some central memory lymphocytes. Remarkably, agonist-primed cells within tumors expressed heightened Tcf7, a transcription factor downstream of the canonical Wnt pathway essential for stemness (20) and directly associated with lymphocytes with durable immunity to cancer (19). Importantly, this altered memory phenotype of cells treated in vitro with a RORγ agonist several months prior were functionally superior to untreated cells and provided protection from repeated tumor challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While mice infused with untreated cells were mainly effectors with some central memory lymphocytes. Remarkably, agonist-primed cells within tumors expressed heightened Tcf7, a transcription factor downstream of the canonical Wnt pathway essential for stemness (20) and directly associated with lymphocytes with durable immunity to cancer (19). Importantly, this altered memory phenotype of cells treated in vitro with a RORγ agonist several months prior were functionally superior to untreated cells and provided protection from repeated tumor challenges.…”
Section: Discussionmentioning
confidence: 99%
“…When lymphocytes from mice receiving LYC-54143–treated Th17 plus Tc17 cells were analyzed after eradicating or controlling tumors, we found that the donor cells were more prevalent and were composed of diverse memory phenotypes compared with mice unfused with untreated cells. In addition, the agonist-primed cells expressed heightened Tcf7, a transcription factor downstream of the canonical Wnt pathway essential for stemness (20) and long-lasting immunity to cancer (19). Importantly, mice cured with LYC-54143–primed cells were protected from repeated tumor challenges several months later.…”
Section: Introductionmentioning
confidence: 99%
“…CAL-101 and Indo blocked Akt phosphorylation and β-catenin expression in Th17 cells, but only temporarily, as these pathways rebounded to a greater extent (compared with untreated cells) after secondary antigen recall responses. Th17 cells treated with both drugs expressed higher lev- els of Tcf7, a critical protein in the Wnt/β-catenin pathway responsible for promoting T cell self-renewal (3,37,(41)(42)(43)(44). Moreover, the treated Th17 cells reexpressed β-catenin and phosphoAkt upon restimulation in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…The first three cell divisions of B cells and T cells also exhibit asymmetry of anabolic signaling between sibling cells, with one sibling cell more proliferative and the other more quiescent [5, 6, 8, 9, 35]. In those early divisions, however, the more activated sibling has yet to silence Pax5 or TCF1 and is, thus, merely specified (in a reversible manner) to be an activated progenitor of plasma cells or effector T cells, respectively [2, 5, 6] (Figure 2).…”
Section: Bifurcating Sibling Cell Metabolism and Cell Fatementioning
confidence: 99%
“…In those early divisions, however, the more activated sibling has yet to silence Pax5 or TCF1 and is, thus, merely specified (in a reversible manner) to be an activated progenitor of plasma cells or effector T cells, respectively [2, 5, 6] (Figure 2). When the activated progenitor produces a daughter with silenced Pax5 or TCF1 alongside a less anabolic sibling that remains a progenitor, the more differentiated cell is determined because of the irreversible nature of the silencing.…”
Section: Bifurcating Sibling Cell Metabolism and Cell Fatementioning
confidence: 99%